British propaganda in the 20th century : selling democracy - Taylor, Philip M. (Edinburgh University Press, 1999)
Philip M. Taylor analyses the period from World War One to the present day and demonstrates how Britain has established a model for the dissemination of democratic propaganda world-wide. His writing covers films, radio, television and the press.
Contains previously published articles, some revised and updated.
Keywords: Propaganda, British -- History -- 20th century.; Great Britain -- Foreign relations -- 20th century.; Democracy -- Public opinion.; Propagande britannique -- Histoire -- 20e siècle.; Grande-Bretagne -- Relations extérieures -- 20e siècle.; SOCIAL SCIENCE -- General.; HISTORY -- Europe -- Great Britain.; Democracy -- Public opinion; Diplomatic relations; Propaganda, British; Great Britain; Militärpolitik; Propaganda; Großbritannien; Propaganda.; Massacommunicatie.; Verenigd Koninkrijk van Groot-Brittannië en Noord-Ierland.; Propaganda -- Storbritannien -- 2000-talet.; Storbritannien -- utrikespolitik -- 2000-talet.; Propaganda, British.; 1900-1999; History